Self-attention based recurrent convolutional neural network for disease prediction using healthcare data. (July 2020) - Usama, Mohd; Ahmad, Belal; Xiao, Wenjing; Hossain, M. Shamim; Muhammad, Ghulam
Highlights: We proposed a new self-attention based recurrent convolutional neural network for prediction of cerebral infarction disease. Experiment results exhibit that the proposed model based on clinical intelligence approach perform appropriate diagnosis for prediction of cerebral infarction disease. .Clinical notes are extracted from real-life hospital dataset to use in experiment. After that, put forward a model which automatically learns high-level semantic features from unstructured clinical text using sliding window convolution approach with the intra-layer recurrent connection. Self-attention mechanism is used to get the focus of the model on essential words which contribute to meaning in the clinical text by using softmax probability distribution at the interior of the model. Abstract: Background and Objective: Nowadays computer-aided disease diagnosis from medical data through deep learning methods has become a wide area of research. Existing works of analyzing clinical text data in the medical domain, which substantiate useful information related to patients with disease in large quantity, benefits early-stage disease diagnosis. However, benefits of analysis not achieved well when the traditional rule-based and classical machine learning methods used; which are unable to handle the unstructured clinical text and only a single method is not able to handle all challenges related to the analysis of the unstructured text, Moreover, the contribution of all words in clinical text is not the same in the prediction of disease. Therefore, there is a need to develop a neural model which solve the above clinical application problems, is an interesting topic which needs to be explored. Methods: Thus considering the above problems, first, this paper present self-attention based recurrent convolutional neural network (RCNN) model using real-life clinical text data collected from a hospital in Wuhan, China. This model automatically learns high-level semantic features from clinical text by using bi-direction recurrent connection within convolution. Second, to deal with other clinical text challenges, we combine the ability of RCNN with the self-attention mechanism. Thus, self-attention gets the focus of the model on essential convolve features which have effective meaning in the clinical text by calculating the probability of each convolve feature through softmax. Results: The proposed model is evaluated on real-life hospital dataset and used measurement metrics as Accuracy and recall. Experiment results exhibit that the proposed model reaches up to accuracy 95.71%, which is better than many existing methods for cerebral infarction disease. Conclusions: This article presented the self-attention based RCNN model by combining the RCNN with self-attention mechanism for prediction of cerebral infarction disease. The obtained results show that the presented model better predict the cerebral infarction disease risk compared to many existing methods. The same model can also be used for the prediction of other disease risks.